The Arrangement of Downtown Area as Effort to Represent Identity of Ambon [Case Study: A. Y. Patty Street Area] - Kreisson Pisty Larwuy; Endang Titi Sunarti Darjosanjoto; Murni Rachmawati (IPTEK Journal of Proceedings Series, 2015)
City is basically an expression of human life which is manifestation in the form of mass and space. This demonstrates the need for the city in terms of the functional aspects. The Downtown area of the city of Ambon is one strategic area, multi-functional and loaded with historical value, which has been badly damaged by the riots. For the study of the arrangement of the this, needs to developed in order to create environment moreover to bring the city's identity as a whole. This research uses historical approach and qualitative descriptive approach. Data was collected and will be analyzed, by using synchronic reading and diachronic reading. The results of this study is to bring back the unique identity of Ambon city, the culture Pela Gandong- Baku Dapa urban communities that have been lost due to social conflict.